MyD88 is essential for alveolar bone loss induced by Aggregatibacter actinomycetemcomitans lipopolysaccharide in mice. (30th July 2013) - Madeira, M.F.M.; Queiroz‐Junior, C.M.; Cisalpino, D.; Werneck, S.M.C.; Kikuchi, H.; Fujise, O.; Ryffel, B.; Silva, T.A.; Teixeira, M.M.; Souza, D.G.
Summary: Aggregatibacter actinomycetemcomitans is a Gram‐negative bacteria highly associated with localized aggressive periodontitis. The recognition of microbial factors, such as lipopolysaccharide from A. actinomycetemcomitans ( Aa LPS), in the oral environment is made mainly by surface receptors known as Toll‐like receptors (TLR). TLR4 is the major LPS receptor. This interaction leads to the production of inflammatory cytokines by myeloid differentiation primary‐response protein 88 (MyD88) ‐dependent and ‐independent pathways, which may involve the adaptor Toll/interleukin‐1 receptor‐domain‐containing adaptor inducing interferon‐β (TRIF). The aim of this study was to assess the involvement of MyD88 in alveolar bone loss induced by Aa LPS in mice. C57BL6/J wild‐type (WT) mice, MyD88, TRIF or TRIF/MyD88 knockout mice received 10 injections of Aa LPS strain FDC Y4 (5 μg in 3 μl), in the palatal gingival tissue of the right first molar, every 48 h. Phosphate‐buffered saline was injected in the opposite side and used as control. Animals were sacrificed 24 h after the 10th injection and the maxillae were removed for macroscopic and biochemical analyses. The injections of Aa LPS induced significant alveolar bone loss in WT mice. In the absence of MyD88 or TRIF/MyD88 no bone loss induced by Aa LPS was observed. In contrast, responses in TRIF −/− mice were similar to those in WT mice. Diminished bone loss in the absence of MyD88 was associated with fewer TRAP‐positive cells and increased expression of osteoblast markers, RUNX2 and osteopontin. There was also reduced tumor necrosis factor‐α production in MyD88 −/− mice. There was less osteoclast differentiation of hematopoietic bone marrow cells from MyD88 −/− mice after Aa LPS stimulation. Hence, the signaling through MyD88 is pivotal for Aa LPS‐induced osteoclast formation and alveolar bone loss.